Fiskerikonsesjoner og rettigheter - Vidar Jarle Landmark (Arctic Review on Law and Politics, 2011)
The right to participate in commercial fishing and allocation of quotas When discussing the rights of the Sami people in relation to the existing Norwegian fisheries management system and fishery policy, knowledge of the legal framework and regulations in force is necessary. This article gives a summary of the Norwegian government’s view of the marine resources as common resources, a brief introduction to the legislation regarding participation in commercial fishery in Norway and the distribution/allocation of quotas according to the act relating to the management of wild living marine resources. The article ends with a discussion of the legal possibilities the change the established allocation of quotas.